O15.3 Evaluation of an Immunochromatographic Point-Of-Care Test For the Simultaneous Detection of Nontreponemal and Treponemal Antibodies in Patients with Syphilis. (13th July 2013) - Castro, R; Lopes, Â
Abstract : Background: We described the evaluation of the DPP Syphilis Screen and Confirm Assay, a point-of-care test (POC) for the simultaneous detection of nontreponemal and treponemal antibodies for the serological diagnosis of patients with syphilis. Methods: A total of 248 samples from patients with active syphilis (173), past syphilis (15) and from individuals considered as no infected by Treponema pallidum (60) were studied with the DPP Syphilis Screen and Confirm, Rapid Plasma Reagin (RPR), and fluorescent treponemal antibody absorption (FTA-Abs) tests. In addition patients with active syphilis cases (36) primary, (39) secondary, and (98) latent, were evaluated. The DPP Syphilis Screen and Confirm device consists of a plastic cassette with a recombinant T. pallidum and a synthetic nontreponemal test line antigens and a procedural control line. Results: The sensitivity of the DPP Syphilis Screen and Confirm, nontreponemal and treponemal tests was 97.6% and 96.8% while the specificity was 94.7% and 93.1% respectively, when compared to the predicates RPR and FTA-abs tests. The treponemal and nontreponemal clinical sensitivity of primaries was 100% (36/36), for both and for secondary syphilis was also 100% (39/39), for both test and predicates. For patients with latent syphilis the sensitivity was 97.96% (96/98) for the treponemal test and 98.98% (97/98) for the nontreponemal test while for the predicates FTA-ABS and RPR was 100% (98/98) and 98.98% (97/98), respectively. With patients without syphilis the specificity of the DPP Syphilis Screen and Confirm test was 91.66% (55/60) for the treponemal line and 96.66% (58/60) for the nontreponemal line. Conclusion: These results indicates that the DPP Syphilis Screen and Confirm POC test could be a useful tool for the serological diagnosis of syphilis, including resource-poor settings where there is a need to provide counselling and treatment on site and thus prevent the further spread of the disease.